Removal of arsenic (III) and (V) from water bodies by using biopolymers via adsorption: A review - Warda Masoom; Ayesha Khan; Amna Sarwar; Sara Musaddiq; Zahoor Hussain Farooqi; Sadia Iqbal (eXPRESS Polymer Letters)
Arsenic, an element found in the Earth’s mantle, can be highly toxic, especially in its As (III) form. It enters our food chain through human activities like melting metals, using arsenic-based pesticides, and natural processes like volcanoes and rock breakdown. Consuming too much arsenic is extremely dangerous, impacting many countries worldwide. To tackle this issue, various methods like filtering, adding chemicals, and using electricity have been developed to clean arsenic-contaminated water. Among these, adsorption is a standout approach due to its simplicity and effectiveness. Biopolymers from living sources offer a natural solution, easily tweaked for arsenic removal. These biopolymers contain functionalities that can strongly latch onto toxic materials, acting like magnets. By customizing them with compounds like titanium dioxide (TiO2), magnetite (Fe3O4), and others, they become even better at capturing arsenic, shaped into tiny particles or beads. This adaptation makes biopolymers a promising choice for cleaning arsenic from water. This review focuses on ways to clean water, specifically exploring how materials like chitosan, alginate, and modified cellulose can be used to remove arsenic by adsorption. It investigates how these materials work under different conditions, highlighting important details. By sharing these insights, this article contributes to the ongoing efforts to ensure cleaner water resources.